SMART CITY POLICY BETWEEN INSTITUTIONS AND CITIZENS: THE PERSPECTIVE OF THE CITY OF MILAN - Mariano Melchionda (Economy and Sociology)
In the environmental and climate issue, a decisive role is played by mobility. In recent years we are witnessing a kind of transportation revolution, especially urban transportation, with a sustainable mobility.